2015
DOI: 10.1038/mtna.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

FASTAptamer: A Bioinformatic Toolkit for High-throughput Sequence Analysis of Combinatorial Selections

Abstract: High-throughput sequence (HTS) analysis of combinatorial selection populations accelerates lead discovery and optimization and offers dynamic insight into selection processes. An underlying principle is that selection enriches high-fitness sequences as a fraction of the population, whereas low-fitness sequences are depleted. HTS analysis readily provides the requisite numerical information by tracking the evolutionary trajectory of individual sequences in response to selection pressures. Unlike genomic data, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
261
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(268 citation statements)
references
References 46 publications
7
261
0
Order By: Relevance
“…It was generally found that activities remained below detection levels until rounds 10-15. In pools displaying bulk polyclonal activity, examination of the most abundant sequences revealed by deep sequencing was sufficient to discover active XNAzymes; it may, however, be possible to identify sequences under enrichment through a more thorough examination of deep-sequencing data 33,34 , thereby reducing the number of rounds of selection required.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was generally found that activities remained below detection levels until rounds 10-15. In pools displaying bulk polyclonal activity, examination of the most abundant sequences revealed by deep sequencing was sufficient to discover active XNAzymes; it may, however, be possible to identify sequences under enrichment through a more thorough examination of deep-sequencing data 33,34 , thereby reducing the number of rounds of selection required.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…3). RT reactions must be performed in order to generate cDNA complementary to the selected XNAzymes (Steps [30][31][32][33], which can then be isolated and PCR-amplified (Steps 34-45), thus allowing the generation of templates for the synthesis of XNA for subsequent rounds of selection (Step 46A; Fig. 4), or sequencing Step 46B.…”
Section: Introductionmentioning
confidence: 99%
“…Preprocessed sequences were then further analyzed using the FASTAptamer toolkit (http://burkelab.missouri.edu/fastaptamer.html) (34). FASTAptamer-Count was used to determine the number of times each sequence was sampled from the population.…”
Section: Methodsmentioning
confidence: 99%
“…[7] Aptamer clustering usually implements low thresholds, ranging from 1 to 5, which corresponds to the number of permissible substitutions, deletions, or insertions that constitute the difference between the aptamers. Clustering during the HT-SELEX analysis with the help of the FASTAptamer set of scripts [8] proceeds as following: First, the number of individual readings for each aptamer is determined, then the normalized value (reads per million [RPM]) is calculated from this number and from the total number of readings, and the aptamers are ranked by their RPM in descending order. Clustering starts from the first, the most enriched aptamer.…”
Section: Original Articlementioning
confidence: 99%